Penerapan Media Pembelajaran Pop-Up Book Dalam Meningkatkan Hasil Dan Minat Belajar Pada Mata Pelajaran PPKn Siswa Kelas V Di UPT SDN Mannuruki Kec. Tamalate Kota Makassar - Parida Parida; Muhajir Muhajir; Rismawati Rismawati (Departement of Mathematics Education, 2024)
This research aims to find out how to increase learning outcomes and interest through the use of Pop Up Book learning media in Civics subjects for class V students at SDN Mannuruki, Kec. Tamalate City, Makassar 2024 academic year. This type of research is classroom action research (PTK). The subjects of this research were 23 class V students. Data collection techniques include observation sheets, test sheets during the learning process, and documentation during learning activities. The research results showed that the pretest results showed that the average student learning score was 75.54 with a high category of 32.15%, namely 5 students in cycle I, while the average student learning score was 90.46% with a very high category of 100%, namely 16. student. Thus, it can be concluded that the use of Pop Up Book learning media is effectively used in PPKn learning for class V students at UPT SPF SDN Mannuruki, Kec. Tamalate, Makassar City.